2017
DOI: 10.1016/j.jfineco.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Are foreign investors locusts? The long-term effects of foreign institutional ownership

Abstract: This paper challenges the view that foreign investors lead firms to adopt a short-term orientation and forgo long-term investment. Using a comprehensive sample of publicly listed firms in 30 countries over the period 2001-2010, we find instead that greater foreign institutional ownership fosters long-term investment in tangible, intangible, and human capital. Foreign institutional ownership also leads to significant increases in innovation output. We identify these effects by exploiting the exogenous variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
186
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 516 publications
(206 citation statements)
references
References 69 publications
17
186
2
1
Order By: Relevance
“…Evidence of a positive relationship between foreign ownership and innovation has been previously found for China by Choi et al (2011), European countries by Falk (2008) and for a worldwide sample of firms by Bena, Ferreira, Matos, and Pires (2017). We find that for Indian firms, foreign ownership is associated with the conditional odds ratio of research-activity being smaller by 800%.…”
supporting
confidence: 68%
“…Evidence of a positive relationship between foreign ownership and innovation has been previously found for China by Choi et al (2011), European countries by Falk (2008) and for a worldwide sample of firms by Bena, Ferreira, Matos, and Pires (2017). We find that for Indian firms, foreign ownership is associated with the conditional odds ratio of research-activity being smaller by 800%.…”
supporting
confidence: 68%
“…For the relevant studies, Aggarwal et al (2011) found that firms with higher institutional ownership are more likely to terminate poorly performing Chief Executive Officers (CEOs) and exhibit improvements in valuation over time, indicating that international portfolio invested by institutional investors promotes good corporate governance practices around the world. Bena et al (2017) argued that greater foreign institutional ownership fosters long-term investment in tangible, intangible, as well as human capital and leads to significant increases in innovation output. Feng, Zhou, and Chan (2014) documented that institutional investors exhibit a smart money effect that can move new money into (out of) future good (poor) performers.…”
Section: Institutional Investorsmentioning
confidence: 99%
“…Recent examples include Bena et al . () and Tarasconi and Menon (). The general term for these approximate methods is probabilistic record linkage , which was first proposed in the seminal work by Fellegi and Sunter ().…”
Section: Introductionmentioning
confidence: 97%